La arquitectura patrimonial del Centro Histórico de Morelia en la conformación de la identidad individual - Luis Leonardo, Ixchel (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
This investigation features a study about the memories of eight writers from Morelia regarding the “Historic downtown Morelia” and the historic analysis of the social process since its foundation in 1541 all the way to the revolution’s following period in the beginning of the twentieth century, the purpose is to understand the relationships and the basic aspects that arcitulate the three large categories: architecture, human identity and cultural heritage, as well as the relationships between individual and collective identity upon the theoretical base of human identity as the development of the potentialities and its application up to self-realization.

La presente investigación comprende un estudio sobre las memorias de ocho escritores morelianos del “Centro Histórico de Morelia” y el análisis histórico del proceso social desde su fundación en 1541 hasta el período posterior a la revolución en los inicios del siglo XX. Lo anterior con el objetivo de entender las relaciones y los aspectos básicos que articular tres grandes categorías: arquitectura, identidad humana y patrimonio cultural; asimismo las relaciones entre la identidad individual y colectiva. Sobre la base teórica de la identidad humana como el desarrollo de las potencialidades y su aplicación hasta la autorrealización.
Facultad de Arquitectura. Maestría en Arquitectura, Investigación y Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-M-2011-0001; Identidad humana; Cosmovisión; Arquitectura virreinal; Mitología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1567